PELATIHAN LITERASI DIGITAL UNTUK MENINGKATKAN PERLINDUNGAN KEAMANAN DI DUNIA MAYA BAGI PARA GURU - Ambarwati, Evi Karlina; Hernawan, Yosep; Dewi, Indah Purnama; Utami, Praditya Putri; Nurwinda, Sulistia; Alqoyyumi, Nabila (Jurnal Abdi Insani, 2024)
Information Communication Technology (ICT) is rapidly developingy. The internet is the newest and most important technology that everyone use as a means of entertainment, communication and social interaction, as well as public health and welfare. However, the increasingly massive use of the internet has an impact on skills in finding, consuming and communicating digital content as well as the security of user data which can be misused by irresponsible parties. In line with developments in learning technology, the government priorities in education digitalization programs,so  teachers need to have digital literacy. The implementation of this Community Service is an assistance in strengthening the competency of RA At-Taqwa Kelapadua Tanjungbungin teachers, Pakisjaya District, Karawang Regency through digital literacy and cyber security training. The results of the activity show that the teachers have digital literacy knowledge in the "good" category in the aspects of Data Literacy, Communication and Collaboration, Digital Content Creation, Problem Solving and Security. Various efforts still need to be made so that teachers' digital literacy can be better through structured teacher professional competency improvement programs and curriculum reform at teacher education institutions.